An evaluation of a common elements treatment approach for youth in Somali refugee camps. (25th April 2018) - Murray, L. K.; Hall, B. J.; Dorsey, S.; Ugueto, A. M.; Puffer, E. S.; Sim, A.; Ismael, A.; Bass, J.; Akiba, C.; Lucid, L.; Harrison, J.; Erikson, A.; et al.
Abstract : Background: This paper reports on: (1) an evaluation of a common elements treatment approach (CETA) developed for comorbid presentations of depression, anxiety, traumatic stress, and/or externalizing symptoms among children in three Somali refugee camps on the Ethiopian/Somali border, and (2) an evaluation of implementation factors from the perspective of staff, lay providers, and families who engaged in the intervention. Methods: This project was conducted in three refugee camps and utilized locally validated mental health instruments for internalizing, externalizing, and posttraumatic stress (PTS) symptoms. Participants were recruited from either a validity study or from referrals from social workers within International Rescue Committee Programs. Lay providers delivered CETA to youth (CETA-Youth) and families, and symptoms were re-assessed post-treatment. Providers and families responded to a semi-structured interview to assess implementation factors. Results: Children who participated in the CETA-Youth open trial reported significant decreases in symptoms of internalizing ( d   =  1.37), externalizing ( d   =  0.85), and posttraumatic stress ( d   =  1.71), and improvements in well-being ( d   =  0.75). Caregivers also reported significant decreases in child symptoms. Qualitative results were positive toward the acceptability and appropriateness of treatment, and its feasibility. Conclusions: This project is the first to examine a common elements approach (CETA: defined as flexible delivery of elements, order, and dosing) with children and caregivers in a low-resource setting with delivery by lay providers. CETA-Youth may offer an effective treatment that is easier to implement and scale-up versus multiple focal interventions. A fullscale randomized clinical trial is warranted.